Research Questions, Concepts & Operationalisation - Ian Hoker (Jurnal Penelitian Pos dan Informatika, 2011)
People frequently confuse the terms hypothesis and theory. They are very different. A hypothesis is very mucha tentative set of statements based on observations – or even hunches and guesses – but there is no body oftested evidence to support them. When does a hypothesis become a theory?